1984
DOI: 10.1021/ja00336a011
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal catalyst-coated semiconductors in surfactant vesicles: in situ generation of rhodium-coated cadmium sulfide particles in dihexadecyl phosphate vesicles and their utilization for photosensitized charge separation and hydrogen generation

Abstract: Mittels Ultraschall werden Dihexadecylphosphat‐Zweischicht‐Vesikel, die adsorbierte Cd‐Ionen enthalten, die mit Rhodium bedeckt sind, erzeugt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 4 publications
3
40
0
Order By: Relevance
“…Fendler and co-workers [246][247][248][249][250] have shown that it is possible to fix the cadmium sulfide colloid particles onto the membranes of surfactant vesicles and have investigated the photochemical and photocatalytic reactions of the fixed CdS in the presence of various electron donors and acceptors. Note, that there is no vectorial transmembrane PET in these systems.…”
Section: Electron Transfer Along Bridging Molecules Molecular Wires mentioning
confidence: 99%
“…Fendler and co-workers [246][247][248][249][250] have shown that it is possible to fix the cadmium sulfide colloid particles onto the membranes of surfactant vesicles and have investigated the photochemical and photocatalytic reactions of the fixed CdS in the presence of various electron donors and acceptors. Note, that there is no vectorial transmembrane PET in these systems.…”
Section: Electron Transfer Along Bridging Molecules Molecular Wires mentioning
confidence: 99%
“…[8][9][10] Synthesis of nanoparticle/ clay composites is very important in the fabrication of such different tools as optical devices, adsorbents, catalysts, sensors, polarizers, color filters, magnetic data storage media, and many others. [11][12][13][14][15][16][17][18] The main characteristics of these nanocomposites are the size and shape of the incorporated metal nanoparticles, as well as the chemical and physical properties of the clay source (ie, ion absorption capacity, active surface area, and interlamellar space). Different techniques can be used to achieve metal/clay nanocomposites, ie, distribution of nanoparticles from chemically produced metal nanoparticles in the clay matrix and by synthesis of metal nanoparticles outside and inside the clay matrix using physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies explored the application of single-compartment vesicles as stabilising matrix for CdS-based photocatalysts [67]. Different strategies for CdS synthesis allowed the formation of the crystals on desired size of the phospholipid bilayer [68].…”
Section: Vesiclesmentioning
confidence: 99%